Strategi Digital UMKM Ayam Rujak Semoga Jaya Perancangan Website dengan GitHub untuk Meningkatkan Promosi Produk - Ramadhani, Dea; Nabella, Mauri; Siti Fatimah J (CV. ITTC INDONESIA, 2024)
The design of the Ayam Rujak Hopefully Jaya website is part of the Project Based Learning (PBL) activities in the Web Design course at Padang State Polytechnic. This website is designed to help MSMEs utilize digital technology to promote their products, especially processed chicken rujak. Through an interactive and informative website, users can easily access information about products, prices, locations, as well as place online orders. This website design uses Visual Studio Code and prioritizes a user-friendly appearance to provide a comfortable shopping experience for customers. It is hoped that with this website, UMKM Ayam Rujak Hopefully Jaya can expand its market reach and increase sales significantly through online platforms, while strengthening business branding in the digital era.